Semiclassical gravitational collapse and avoidance of singularities - Malafarina, D. (Nazarbayev University, 2014)
General Relativity (GR) predicts that, under standard conditions for normal matter, when gravity prevails over other forces, a space-time singularity must form [1]. On the other hand singularities are not expected to occur in the real universe as they may lead to pathological problems for the causal structure of the space-time. Several recent studies suggest that there may be mechanisms that prevent the formation of singularities and that these are likely to be related to quantum correction to GR that appear in the strong field regime. We considered some mathematical toy models describing complete gravitational collapse of a massive cloud that classically lead to the formation of a singularity. In order to fully characterize the final stages of collapse we would then need to use a theory of quantum-gravity which we do not possess yet. On the other hand semi-classical approaches are possible and they provide valuable hints at how gravity behaves in such extreme conditions [2].
Keywords: gravitational collapse; singularities; mechanisms; models; quantum-gravity; conditions; conditions